2017
DOI: 10.1177/1090198116683141
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Mediating the Effect of the CHoBI7 Intervention on Handwashing With Soap: A Randomized Controlled Trial

Abstract: Inadequate hand hygiene is estimated to result in nearly 300,000 deaths annually, with the majority of deaths being among children younger than 5 years. In an effort to promote handwashing with soap and water treatment behaviors among highly susceptible household members of cholera patients, we recently developed the Cholera-Hospital-Based Intervention-for-7-Days (CHoBI7); chobi means picture in Bengali. This 1-week handwashing with soap and water treatment intervention is delivered by a promoter in the hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 42 publications
4
21
1
Order By: Relevance
“…Using a theory-based approach, the CHoBI7 intervention program was informed by components of Protection Motivation Theory, IBM-WASH, and the RANAS Model [25, 27, 29]. Using these theories and models, we developed behavior change techniques for the CHoBI7 intervention program targeting remembering, perceived susceptibility and severity, cholera awareness, disgust, response efficacy, convenience, and self-efficacy (based on previous studies [18, 21, 30, 41–43]), and used Likert scale statements to measure these psychosocial factors (methods are published in George et al [44]). By measuring these psychosocial factors during our recent RCT of CHoBI7, we were able to investigate the underlying mechanism of change that led to the high handwashing with soap behavior observed among intervention participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a theory-based approach, the CHoBI7 intervention program was informed by components of Protection Motivation Theory, IBM-WASH, and the RANAS Model [25, 27, 29]. Using these theories and models, we developed behavior change techniques for the CHoBI7 intervention program targeting remembering, perceived susceptibility and severity, cholera awareness, disgust, response efficacy, convenience, and self-efficacy (based on previous studies [18, 21, 30, 41–43]), and used Likert scale statements to measure these psychosocial factors (methods are published in George et al [44]). By measuring these psychosocial factors during our recent RCT of CHoBI7, we were able to investigate the underlying mechanism of change that led to the high handwashing with soap behavior observed among intervention participants.…”
Section: Introductionmentioning
confidence: 99%
“…By measuring these psychosocial factors during our recent RCT of CHoBI7, we were able to investigate the underlying mechanism of change that led to the high handwashing with soap behavior observed among intervention participants. Response efficacy (judgments about the efficacy of a preventive response that will avert the perceived threat [29]) was found to mediate the intervention’s effect on handwashing with soap habit formation at the 1-week follow-up, whereas disgust, convenience, and cholera awareness were mediators of habit maintenance at the 6 to 12-month follow-up [44]. Our study was the first RCT of a WASH intervention that conducted a mediation analysis to investigate the underlying mechanism of change in a low-income country.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, in our recent analysis of psychosocial factors associated with handwashing with soap in the RCT of CHoBI7, we found disgust messages focusing on feces as a transmission route for cholera to significantly mediate the effect of the CHoBI7 intervention at the 6-to 12-month follow-up. 29 Therefore, CHoBI7 presents an effective approach to increase awareness on key times for handwashing with soap, transmission routes for cholera, and observed handwashing with soap behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the RANAS theory of behaviour argue that it is common for health promotion messages in emergency settings to focus on increasing the 'perceived susceptibility and perceived severity of contracting a disease, and factual knowledge about the possibility of being affected' [33] p.561, forgetting other behavioural factors that are also important predictors of behaviour. Other studies have even shown that behaviour can change during disease outbreaks without people feeling any increased sense of infection risk [55].…”
Section: Limited Attention To Behavioural Determinantsmentioning
confidence: 99%